ANALISIS POTENSI DAN EFEKTIVITAS PENERIMAAN DAN PEMUNGUTAN PAJAK MINERAL BUKAN LOGAM DAN BATUAN SEBAGAI SUMBER PENDAPATAN ASLI DAERAH (PAD) DI KABUPATEN MINAHASA UTARA - Tesalonika, Moningka; Poputra, Agus T.; Mawikere, Lidia (Universitas Sam Ratulangi, 2016)
Taxes are the country's largest source of financing in national development. This study purposed to analyze the potential and effectiveness of Non Metallic Minerals and rocks tax, as a source of regional revenue in North Minahasa District. The analytical method used is descriptive qualitative method, using primary data and secondary data. The results showed that the potential tax increases every year, the level of effectiveness of the Metallic Minerals Tax and rocks in 2012 - 2015 meet the criteria for highly effective, the highest level of effectiveness achieved in 2013 with a percentage of 111% to the target and the realization of very large. In 2015 the tax revenue Metallic Minerals and Rocks that most large compared with previous years. Improved performance of the employees to optimize each of the duties and responsibilities in the process of collecting that tax revenue Metallic Minerals and rocks can be more effective in the future. Keyword :mineral tax, local revenue, potential and effectiveness